Natural and anthropogenic disturbances shape benthic phototrophic and heterotrophic microbial communities in the Po River Delta system. (30th June 2019) - Cibic, Tamara; Fazi, Stefano; Nasi, Federica; Pin, Lorenzo; Alvisi, Francesca; Berto, Daniela; Viganò, Luigi; Zoppini, Annamaria; Del Negro, Paola
Abstract: This study represents the first example in which benthic heterotrophic and photoautotrophic microbial communities (prokaryotes and microphytobenthos-MPB, respectively) were simultaneously investigated. To explore how they synergistically respond to multiple natural and anthropogenic stressors, in the framework of the Project RITMARE four lagoons of the Po River Delta were sampled in May 2016: two with more marine features, i.e. Scardovari (SC) and Caleri (CL), and two more directly affected by the Po River flow, i.e. Canarin (CN) and Vallona-Marinetta (MV). The abundance and structure of benthic communities were related to physical-chemical parameters i.e. grain-size, total N, total organic C, stable C and N isotopes, and synthetic organic contaminants. Stations were gathered into three distinct groups (Ransosim  = 0.540 p < 0.001) according to their different physical-chemical features: outer, inner-freshwater and inner-marine sites. Contamination levels did not seem to severely affect the microbial abundances that were overall stimulated by the combined effect of high organic and nutrient loads: prokaryotes up to +42% and MPB up to +93%. Bacteria and Archaea displayed high densities at sites directly influenced by the freshwater input and anthropogenically derived nitrogen. Delta- (30.8%), Alpha- (12.8%), Gamma- (11.8%) and Beta-Proteobacteria (7.1%) were the dominant classes at all sites. For both communities, a significant inter-lagoonal (among different lagoons) and intra-lagoonal (among stations within the same lagoon) pattern was highlighted by PERMANOVA. nMDS and SIMPER analyses revealed distinct assemblages in the inner and outer parts of the lagoons. We applied a novel functional approach based on diatom life modes. At inner and outer sites, different diatom living forms developed: epipsammic (on sand) nearby the lagoonal mouths, epipelic (on mud) at the innermost sites and non-benthic forms (planktonic, tychopelagic and epiphytic) at sites directly influenced by freshwater. Distance-based Linear Models further indicated that salinity, clay and temperature were the significant drivers of the prokaryotic spatial distribution whereas clay, PAHs, PCBs and salinity best explained the MPB structure. The dominance of non-benthic diatom life modes in the more polluted lagoon (CN) suggests a negative influence of contamination on the MPB structure. Two diatom keystone species likely contribute to restore the oxic gradient in sediments frequently exposed to anoxia, allowing the subsequent microbial aerobic degradation and the recolonization of higher trophic organisms. The capacity of re-oxygenation after anoxia has important ecological and economic implications in lagoons exploited for aquaculture. Highlights: We simultaneously studied Prokaryotes and MicroPhytoBenthos in four Po River lagoons. Organic and nutrient loads stimulated Prokaryotes (+42%) and MPB (+93%) densities. We found significant inter- and intra-lagoonal patterns for both Prokaryotes and MPB. Salinity, clay and temperature best explained prokaryotic spatial distribution. Clay, PAHs, PCBs and salinity were significant drivers of MPB composition.